Smooth control strategy for emergency switching of multi-port flexible interconnected distribution system modes - Pang, Dan; Yin, Yu; Wang, Zhipeng; Ge, Jinming; Wang, Wei; Wang, Zhenhao; Yi, Hongyin; Zhuang, Yan (Frontiers in Smart Grids, 2024)
The interconnection of distribution networks and flexible multi-state switches (FMSS)is one of the main ways to build a new distribution network with distributed energy sources. After a feeder fault occurs in a multi-port flexible interconnected distribution system, the FMSS can quickly restore power supply to the loads in the lost area through its own mode switching. For the voltage and current impacts and power fluctuations brought about by the mode switching process, this paper proposes an improved state tracking control method, which can effectively alleviate the above impacts and fluctuations; secondly, for the feeder faults connected to the fixed dc bus voltage (Udc-Q) control port, a re-selection method for the Udc-Q control port at the main station is proposed, whereby the port with the highest comprehensive evaluation score is selected to switch to the Udc-Q control mode. Udc-Q control mode to continue to maintain the stability of the DC bus voltage. Finally, the effectiveness of the proposed control strategy is verified in the MATLAB/Simulink simulation platform, which improves the safe and stable operation of the flexible interconnected distribution system under emergency fault conditions.